Fatal splenic sequestration crisis in adult sickle cell-beta thalassaemia. Issue 792 (October 1991) - van Rhee, F.; Balsitis, M.; French, E. A.
Abstract : Fatal acute splenic sequestration crisis in an adult patient with sickle cell-beta+ thalassaemia is described. To our knowledge fatal splenic sequestration in adult sickle cell-beta thalassaemia has not been previously reported.